Information Media Preferences of Goat and Sheep Farmers in Daerah Istimewa Yogyakarta Province - A’yun, Annisa’ Qurrotun; Guntoro, Budi; Sulastri, Endang; Asrianto, Noor (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
Goats and sheep are small ruminants with positive growth values in Daerah Istimewa Yogyakarta Province (DIY). Goats and sheep development in DIY is necessary since these two livestock might be profitable to farmers. Information media have a significant role in disseminating knowledge and innovation to farmers quickly and effectively. However, information access fulfillment for the farmers is the weakness of livestock development. The aims of this research are to analyze farmers’ information media preferences and the factors influencing them. The information media in this study are dummy, namely person media with code zero (0) and ICT media with code one (1). The data was collected through a survey method that involved face-to-face structured questionnaire interviews to goat and sheep farmers in DIY who have at least one year of experience raising goat and or sheep. Farmers in DIY used personal media as their primary information source (86.42%), with fellow farmers being the most popular choice among farmers. Only 13.58% of farmers choose ICTs, with mobile phones being the preferred ICT over computers, radio, and television. The preference for using ICT is influenced by farmer characteristics: age (p < 0.01), livestock experience (p < 0.05), costs (p < 0.1), and ICT number (p < 0.05). Information dissemination using ICT media will be more appropriate for young farmers who are just starting their business.